Vitamin D deficiency and risk of recurrent aphthous stomatitis: updated meta-analysis with trial sequential analysis - Al-Maweri, Sadeq Ali; Al-Qadhi, Gamilah; Halboub, Esam; Alaizari, Nader; Almeslet, Asma; Ali, Kamran; Osman, Safa A. Azim (Frontiers in Nutrition, 2023)
Background: Growing evidence suggests a significant association between vitamin D deficiency and RAS. Hence, the present meta-analysis and trial sequential analysis sought to investigate the potential association between low serum vitamin D levels and RAS. Methods: PubMed, Scopus, Embase, and Web of Science were comprehensively searched on December 1st, 2022 to retrieve all relevant studies. The grey literature was also searched via ProQuest. All case-control studies on the association between vitamin D and RAS were considered. The quality appraisal of the included studies was done using Newcastle-Ottawa scale. RevMan 5.0 and trial sequential analysis (TSA) programs were used for analyses. Results: A total of 14 case-control studies with 1468 subjects (721 RAS patients and 747 controls) were included. The pooled data revealed a significant association between low serum levels of vitamin D and the risk of RAS (mean difference = − 8.73, 95% CI: – 12.02 to – 5.44, I 2 = 94%, P < 0.00001). Additionally, TSA findings indicated that the current studies surpassed the required information size, confirming that the differences were reliable. Conclusion: The available evidence suggests that Vitamin D deficiency may have a role in the pathogenesis of RAS. Therefore, evaluation of vitamin D should be considered in RAS patients. Additionally, the results support the possibility of using vitamin D supplements in the management of RAS patients with inadequate serum levels of vitamin D. Future interventional studies are required to evaluate the benefits of vitamin D replacement in prevention and treatment of RAS.